Manifestations and repercussions of climate change on the oases in Mauritania, “The oases of Adrar Province are a model" (Journal of Libya for geographical studies, 2025)
The oasis area of Mauritania is of exceptional cultural, economic and social importance. In ancient times, cities and urban centres grew around oases and contributed to the prosperity of many economic and cultural activities between the north and south of the Sahara. The desert climate that characterizes the deserts of Mauritania and the wilaya of "Adrar", in particular has contributed to the growing dependence of the population on their livelihoods and stability by building on these oases. However, as the effects of recent climate change are increasing, Mauritanian space is burdened by profound radical environmental and human transformations, most parts of Mauritanian space have been printed, and its host areas have had a significant share.In this article, we will try to highlight the most visible manifestations and impacts of climate change and associated migration and displacement at the level of the oases in wilaya of Adrar, which are an important example. We adopted to study these changes, analyzing a climate database for a significant reference period, spanning from 1940 to 2019. For the migration and population data, we adopted the results of the general population and housing censuses for the years (1988, 2000, 2013, and 2023) of the National Bureau of Statistics.Addressing the study theme demonstrated the most important manifestations and impacts of climate change on oases wilaya of Adrar; resulting from droughts, increasing desertification conditions and migration of the working-class Poor living conditions and lack of infrastructure and social services for the oasis population; all this has contributed to the deterioration of oases in the state in general.
Keywords: Oasis; climate change; migration; economic activities; Mauritania